STUDENTS’ RESPONSES TOWARD THE USE OF WHATSAPP IN LEARNING - Armeria Wijaya (Siliwangi University, 2018)
Lecturing along with the use of whiteboard combined with power point presentation has been traditional practice in classroom. The desired learning outcome has long been examined. Overviewing the postulation by Bransford, Browning, and Cocking (1999, p194) which premise that technology plays significant role for yielding learning environments that advance the possibilities of one-way communication media, such as movies, documentaries, television shows, and music into new areas that require interactive learning like visualizations and student-created content, lead me into an implementation of media development in teaching. This paper aims to see the students’ responses toward the use of WhatsApp in English learning as this smart phone application has been used in some courses in some levels of students in Muhammadiyah University of Surabaya majoring English. Elaborated qualitatively, this paper shows you how much students get into the learning. It is shown that even though self-effort to internet access was the main obstacle in the learning, their reading and writing skills were found improved. This result in the future is expected to be able to make other faculties realize that smart phone application can enhance the learning environment and outcome